2019
DOI: 10.1111/socf.12515
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping Online? Internet News, Social Media, and the Racial Typification of Crime

Abstract: A substantial body of research indicates that television news consumption is associated with criminal stereotyping. However, less is known about how online media, such as Internet news and social media news consumption, is associated with such attitudes. Using a multisite sample of mostly young adults, the current study examines the relationships between multiple types of online news consumption and crime news engagement on racially typifying African Americans as violent, property, and drug offenders. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
(196 reference statements)
2
8
1
Order By: Relevance
“…Thus, hypotheses 2 and 3 are accepted. Those findings are consistent with the normative arguments and epistemological findings highlighted in the existing literature related to internet-based deviant behaviours, such as cyber-loafing [ 78 ], cyberbullying [ 72 , 79 ], racial typification [ 70 ], and cyber-ostracism [ 81 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, hypotheses 2 and 3 are accepted. Those findings are consistent with the normative arguments and epistemological findings highlighted in the existing literature related to internet-based deviant behaviours, such as cyber-loafing [ 78 ], cyberbullying [ 72 , 79 ], racial typification [ 70 ], and cyber-ostracism [ 81 ].…”
Section: Discussionsupporting
confidence: 90%
“…Convergent validity was assessed based on the data from Study 2 ( n = 511) with other construal-level scales reported. Based on the existing literature on cybercrime and cyberbullying, we expected the CRIT to be positively related to problematic internet usage [ 3 , 35 , 70 ] and negative relationship satisfaction [ 35 , 71 , 72 ]. Hence, the following well-established measures were used: the Problematic Internet Use Questionnaire (PIUQ) [ 73 , 74 , 75 , 76 ] and the Negative Semantic Dimension (NSD) from the Positive and Negative Semantic Dimensions of Relationship Satisfaction (PN-SMD) scale [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…Third, the current study would test the moderating role of direct media consumption on these associations. That is, in line with prior research (Dixon, 2008b;Intravia & Pickett, 2019), the links between the salience of the war and ethnic prejudice would be stronger and significant among adolescents who more often rely on these media outlets as a source of information.…”
Section: The Present Studysupporting
confidence: 81%
“…On the other hand, some researchers claimed that exposure to only radicalized groupthink and conformity on social media can increase stereotyping such that social media may reproduce stereotypes and marginalization (Dobson & Knezevic, 2018). In fact, social media and television news increase stereotyping African Americans as criminals because they sometimes fit negative stereotypical information of the group (Intravia & Pickett, 2019). Offensive content and online aggression on social media reinforces feminine stereotypes, resulting in harmful consequences for females (Felmlee, Inara Rodis, & Zhang, 2020;Bailey et al, 2013).…”
Section: Social Mediamentioning
confidence: 99%